Pengaruh Konsentrasi NaOH terhadap pH, Kadar Protein Putih Telur dan Warna Kuning Telur Pidan (Jurnal Ilmu dan Teknologi Hasil Ternak, 2017)
The purpose of this research was to determine the best treatment NaOH addition on pidan eggs. The materials used for this research was pidan made from duck egg, NaOH, salt, black tea and water. The method was used experiment laboratory and Completely Randomized Design (CRD) using 4 treatments and 4 replications. The treatments were T0 (control), T1 (1.4%), T2 (2.8%) and T3 (4.2%). The data were analyzed by Analysis of Variance (ANOVA) if there was significantly continued by Duncanâ€™s Multiple Range Test (DMRT). The result showed that NaOH concentration on pidan eggs gave significant effect (P<0.05) on albumen protein content, gave highly significant (P<0.01) on pH value and yolk colour. The conclusion of this research was 4.2% NaOH addition on pidan egg was the best treatment with gave result yolk and albumen pH: 10.69; 10.25, albumen protein content 26.89%, egg yolk colour L* (lightness), a* (redness), b* (yellowness):Â  26.89; 11.33, and 26.77. The suggestion of this research was ussed different immersion time on pidan egg production.